Plasmapheresis for Pembrolizumab-Induced Hepatitis in a Patient with Squamous Cell Carcinoma and Prior Orthotopic Liver Transplantation. (21st January 2022) - Al-Nattah, Sanaa; Lata Sharma, Kusum; Caldis, Matthew; Spengler, Erin; Nicholas Rose, William
Abstract : Checkpoint inhibitor therapy with monoclonal antibodies against programmed cell death protein 1 (PD1) has been implemented in the treatment of numerous malignancies. Pembrolizumab is one such medication. While severe toxicities are very rare, mild immune-mediated reactions with a variety of end organ injuries are among the most commonly encountered adverse events attributed to these medications. Acute liver injury manifesting as biochemical abnormalities with or without synthetic dysfunction is one such potential adverse reaction. Rarely, a relatively severe hepatitis can occur. While such severe adverse events are often successfully managed with systemic corticosteroids and drug discontinuation, our patient was refractory to standard management. We present a case of pembrolizumab-induced hepatitis in a patient with squamous cell carcinoma and prior orthotopic liver transplantation. Through a combination of serial plasmapheresis and intravenous immunoglobulin(IVIG) infusion, the patient's hepatitis resolved as evidenced by virtual normalization of his liver indices. This illustrates the effectiveness of a relatively novel treatment strategy for this rare side effect of checkpoint inhibitor antineoplastic therapy.